Vitamin D on Early Stages of Diabetic Kidney Disease: A Cross-sectional Study in Patients with Type 1 Diabetes Mellitus - Felício, João Soares; Luz, Rafael Mendonça; de Melo, Franciane Trindade Cunha; de Souza Resende, Fabricio; de Oliveira, Alana Ferreira; Peixoto, Amanda Soares; Abrahão Neto, João Felício; Carvalho, Carolina Tavares; da Silva, Denisson Dias; Santos, Marcia Costa dos; de Queiroz, Natércia Neves Marques; de Lemos, Manuela Nascimento; et al. (Frontiers in Endocrinology, 2016)
Context: Genetic and environmental factors are involved in the pathogenesis of type 1 diabetes mellitus (T1DM), and vitamin D deficiency appears as a candidate to risk factor for developing diabetic kidney disease (DKD). Objective: The purpose of study was to evaluate the existence of an association between low levels of vitamin D and the presence and degree of DKD in T1DM. Patients and methods: We performed a cross-sectional study, between November 2014 and December 2015. Levels of 25(OH)D and albuminuria were analyzed in 37 patients with T1DM and normal glomerular filtration rate. Thirty- six subjects were evaluated as a control group. Results: Patients with T1DM and hypovitaminosis D had higher levels of albuminuria compared to those with normal vitamin D levels (albuminuria (log10) = 1.92 vs 1.44; p <0.05). When we have separated the group of patients according to stage of DKD in patients with normo, micro and macroalbuminuria, there are lower levels of 25(OH)D in the last when compared to the first two groups (26.7 ± 6.2, 24.8 ± 7,0 and 15.9 ± 7.6 ng/ml; p <0.05, respectively). In T1DM group, we have found correlations between vitamin D levels and both albuminuria and DKD stages (r= -0.5, p <0.01 and r= -0.4; p <0.05, respectively). A simple linear regression model, with albuminuria as the dependent variable and vitamin D as an independent variable, showed r2= 0.2 and p <0.01. Conclusions: Our data suggest an association between reduced levels of vitamin D and the presence and severity of DKD.